Utilization of Natural Extracts as Corrosion Inhibitors in the Seawater Environment - Alam, Pocut Nurul; Rosnelly, Cut Meurah; Karo karo, Justaman Arifin; Ilhamdi, Akhar; Soekarno, Raiyan; Aslam, Izzan Nur (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2021)
Infrastructures in coastal area are mostly made of metal which is susceptible to corrosion due to direct contact with the seawater. The Seawater greatly affects the corrosion rate of metals because it contains chloride ions which can penetrate metal surface. The process of corrosioncan beinhibited or slowed by decreasing the corrosion rate in one way, namelythe addition ofcorrosion inhibitors derived from natural materials containing tannin compounds. This study proposed organic corrosion inhibitors which were derived from natural material extracts (coffee leaves andcatappaleaves), the effect of time variations on the efficiency of organic inhibitors was investigated, and the efficiency of each inhibitor organic was compared. The corrosion rate with and without inhibitors was analysed by using the method of weight loss. The results showed that the corrosion rate canbe reducedby adding the natural ingredients extract. The addition of 2% concentration coffee leaves extract resulted in the lowest corrosion rate with the addition of 0.00226 mmpy. The addition ofcatappaleaves extract concentration as much as 2% yield the lowest corrosion rate with the addition of 0.0012 mmpy. The highest efficiency of inhibition system was obtained by using 2%catappaleaves extract at 14 days soaking time at 69.23%, and the lowest by using 1% coffee leaves extract.